The hero’s new "plot" - Matas Pons, Alex (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The relationship between literature and urban geography at a time of changes and breakdowns in modern times are very complex. Hovewer, some of them can be understood. For instance, one of them is about some main protagonist’s in a novel who doesn’t any longer serve the general adventure and a moving unstable scene which doesn’t admit those classic Bakhtin’s chronotopes of the frontiere and the path. Since then, the novel’s plot is the urban scene and the peripatetic hero and his dwellings play the leading role in what the english critic Raymond Williams wrote about Charles Dickens called «the novel as a form».